Postoperative Bowel Function and Related Factors in Enhanced Recovery Protocol with Patients Undergoing Hepatectomy - Hiltunen, Anna-Maria (fi=Turun yliopisto|en=University of Turku|, 2016)
Patients’ bowel dysfunction is a major factor that weakens the results of surgical care as it can cause pain and weaken patients’ rehabilitation. Bowel dysfunction is a common postoperative problem, yet most incidents remain undocumented. The nursing profession has a significant role in enhancing the bowel function postoperatively. However, studies of postoperative bowel function after hepatectomy are scarce and somewhat incongruous. Enhanced recovery protocols are innovative models of care aiming for better outcomes of surgical care. Enhanced recovery protocols can improve gastrointestinal function after surgery, yet patients are also known to be satisfied with their care. The aim was to investigate if postoperative bowel function day varies between patients in terms of age, gender, ASA score, type of surgery, histology, patients’ experienced pain and experienced satisfaction three days after discharge and three months after operation in patients undergoing hepatectomy. The goal was to produce information for basis of scientific research, to give nurses in clinical setting more tools to work with hepatectomy patients undergoing enhanced recovery protocol and to produce information to nurse managers to use in process management of patients undergoing enhanced recovery protocol. The design of this study is descriptive. Data was collected retrospectively from hepatectomy patients (n = 134) undergoing enhanced recovery protocol within the first year of enhanced recovery protocol implementation. The data was based on registers and analyzed statistically. Mean age of patients was 62 years and mean day of discharge was 4. Main (n = 72) histology of the patients was colorectal liver metastases. Mean bowel function day was 3. Most of the patients were very satisfied or satisfied with the care three days after discharge (99%) and three months (90%) after operation. Most of the patients (72%) experienced moderate pain three days after discharge, but three months after operation 47% of the patients did not experience pain and 48% experienced moderate pain. There were no statistically significant differences in bowel function between different age groups, genders, ASA score groups or histologies. Neither were there statistically significant differences in postoperative bowel function in terms of experienced satisfaction or pain. There were statistically significant differences in postoperative bowel function between different types of surgery (p < 0.01). Nurses should take into consideration hepatectomy patients’ type of surgery and pay special attention in supporting major open hepatectomy patients’ postoperative bowel function. Nurses should educate patients undergoing major open hepatectomy about prolonged postoperative bowel function.

Suolentoimintaongelmat ovat keskeinen kirurgisen hoidon tuloksia huonontava tekijä, mikä voi aiheuttaa potilaalle kipua ja heikentää kuntoutumista. Leikkauksenjälkeiset suolentoimintaongelmat ovat yleisiä ongelmia, mutta iso osa tapauksista jää dokumentoimatta. Hoitotyöllä on keskeinen rooli potilaan suolentoiminnan edistämisessä leikkauksen jälkeen, vaikka tutkimustulokset aiheesta ovat vähäisiä ja osittain ristiriitaisia. Optimoidun toipumisen ohjelmat ovat innovatiivisia hoitomalleja, joiden tavoitteena on parantaa kirurgisen hoidon tuloksia. Optimoidun toipumisen ohjelmat voivat parantaa suoliston toimintaa leikkauksen jälkeen, ja potilaiden tiedetään olevan tyytyväisiä niihin. Tarkoituksena oli selvittää, vaihteleeko optimoidun toipumisen ohjelmalla hoidettujen potilaiden leikkauksenjälkeinen suolentoimintapäivä riippuen potilaiden iästä, sukupuolesta, ASA-luokasta, leikkaustyypistä, histologiasta tai potilaan kokemasta kivusta ja tyytyväisyydestä kolme vuorokautta kotiutuksesta tai kolme kuukautta leikkauksen jälkeen. Tavoitteena oli tuottaa tietoa jatkotutkimuksen pohjaksi, antaa kliinisessä työssä työskenteleville hoitajille lisää työkaluja optimoidun toipumisen ohjelmalla hoidettavien maksaresektiopotilaiden hoitamiseen ja tuottaa tietoa hoitotyön esimiehille optimoidun toipumisen ohjelman prosessin johtamiseen. Tutkimus toteutettiin kuvailevalla asetelmalla. Aineisto kerättiin retrospektiivisesti maksaresektiopotilaiden (n = 134) hoidosta ensimmäisen optimoidun toipumisen ohjelman käyttövuoden ajalta. Aineisto kerättiin potilasrekisteristä ja analysoitiin tilastollisesti. Potilaiden keski-ikä oli 62 vuotta ja keskimääräinen kotiutuspäivä oli 4. Suurimmalla osalla potilaista (n = 72) taustalla oli kolorektaalimetastaasit. Keskimääräinen suolentoimintapäivä oli 3. Suurin osa potilaista koki olevansa erittäin tyytyväinen tai tyytyväinen hoitoonsa kolme vuorokautta kotiutuksesta (99 %) ja kolme kuukautta leikkauksesta (90 %). Suurin osa potilaista koki jonkin verran kipuja kolme vuorokautta kotiutuksesta (72 %), mutta kolme kuukautta leikkauksesta 47 % potilaista ei kokenut kipua ja 48 % potilaista koki jonkin verran kipuja. Tilastollisesti merkitseviä eroja suolen toiminnassa ei löydetty riippuen iästä, sukupuolesta, ASA-luokasta, histologiasta, kivusta tai tyytyväisyydestä kolme vuorokautta kotiutumisesta tai kolme kuukautta leikkauksesta. Eri leikkaustyyppien välillä oli tilastollisesti merkitseviä (p < 0.01) eroja suolen toiminnassa. Hoitajien tulisi huomioida potilaalle tehdyn leikkauksen laajuus ja kiinnittää erityistä huomiota isoissa maksaresektioissa olleiden potilaiden suolentoiminnan tukemiseen erilaisilla hoitotyön menetelmillä. Hoitajien tulisi ohjata isoissa maksaresektiossa olleita potilaita leikkauksenjälkeiseen suolentoiminnan hidastumiseen liittyen.
Leikkauksenjälkeinen suolentoiminta ja siihen liittyvät tekijät optimoidun toipumisen ohjelmalla hoidetuilla maksaresektiopotilailla